Regency Hospital Limited (B) : the road travelled - Gupta, Parvinder; Gupta, Nirmal (London : SAGE Publications Ltd, 2017)
A lot had changed at Regency Hospital Limited (RHL) by December 2009 when the case writers visited it after almost nine years. The founder Dr. Atul Kapoor was looking younger and rejuvenated! A sense of enthusiasm was evident all around. RHL had finally become debt free and was making profits. Dr. Kapoors focus was now on initiating and finalizing some of the expansion plans at RHL.
Originally published: Gupta, P., & Gupta, N. (2014). Regency Hospital Limited (B): The road travelled. OB0205(B). Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Regency Hospital Limited (RHL); Hospitals -- Business management -- India -- Case studies; Health services administration -- India -- Case studies; Hospitals -- Administration -- India -- Case studies